Investigating Anxiety in Speaking among EFL Students: A Qualitative Study - Khafidhoh Khafidhoh; Rifky Dora Wijayati; Sarah Hizza Risa (Universitas Ahmad Dahlan, 2023)
This study investigates the causes of anxiety in speaking among EFL students and provides solutions to overcome them. A total of 33 students from the sixth semester of the English Education Department at Universitas Ahmad Dahlan participated in this descriptive qualitative research by completing questionnaires and interviews. The results revealed that nervousness, trembling, and shyness are causing anxiety among students in speaking English, and preparation, confidence, peer-seeking, and effort can help overcome speaking anxiety. The implication of the study suggests that language educators should be aware of the causes of anxiety in EFL students and provide appropriate solutions to help them overcome their speaking anxiety. Limitations of the study may include the relatively small sample size and the fact that the study only focused on sixth-semester students in one particular department at a single university. Therefore, the findings may not be generalizable to other populations or contexts. For future research, it would be useful to include a more extensive and diverse sample of participants from different levels of language proficiency and different educational backgrounds. Additionally, incorporating other data collection methods, such as observation or focus groups, could provide a more comprehensive understanding of the factors contributing to speaking anxiety among EFL students. Finally, exploring the effectiveness of different interventions or strategies to reduce speaking anxiety could be an interesting avenue for future research.